A measurement of B(D+S → φl+ν) B(D+S → φπ+) - CLEO Collaboration (Institutional Knowledge at Singapore Management University, 1994)
Using the CLEO II detector at CESR, we have measured the ratio of branching fractions B(D → φlν) B(D → φπ) = 0.54 ± 0.05 ± 0.04. We use this measurement to obtain a model dependent estimate of B(D → φπ). © 1994.